1999
DOI: 10.1046/j.1365-2249.1999.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal immune priming in onchocerciasis—Onchocerca volvulus-specific cellular responsiveness and cytokine production in newborns from infected mothers

Abstract: This study investigated the effect of maternal Onchocerca volvulus infection on humoral and cellular responsiveness in newborn children and their mothers. Onchocerca volvulus-specific IgG isotypes and IgE were significantly elevated in infected mothers and their infants. One year post partum, O. volvulus-specific IgG4 was strongly reduced in children of infected mothers, while IgG1 responses weakened only slightly. Umbilical cord mononuclear blood cells (UCBC) and peripheral blood cells (PBMC) from mothers pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 41 publications
7
47
0
Order By: Relevance
“…3,4,6,7,19 The intravascular location of schistosomes ensures that antigens excreted or secreted by worms and eggs directly enter the maternal vasculature. 14,26,37 These antigens may thus reach the placenta and the fetal vessels.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3,4,6,7,19 The intravascular location of schistosomes ensures that antigens excreted or secreted by worms and eggs directly enter the maternal vasculature. 14,26,37 These antigens may thus reach the placenta and the fetal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that in disease-endemic countries total 3,7,10,12 and filarial antigen-specific 3,7,10,12 fetal IgE production occurs. Only one investigation 6 demonstrated a direct correlation of enhanced cord blood helminth antigen-specific IgE levels with the corresponding maternal helminth (Onchocerca volvolus) infection, and other studies found no correlation. 7,10 There are few studies regarding the priming of the fetal humoral immune system as a result of maternal schistosome infection.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations